Effects of Intraoperative Fluid Balance During Liver Transplantation on Postoperative Acute Kidney Injury: An Observational Cohort Study. Issue 7 (July 2020) - Carrier, François Martin; Chassé, Michaël; Sylvestre, Marie-Pierre; Girard, Martin; Legendre-Courville, Lancelot; Massicotte, Luc; Bilodeau, Marc
Abstract : Background: Liver transplant recipients suffer many postoperative complications. Few studies evaluated the effects of fluid management on these complications. We conducted an observational cohort study to evaluate the association between intraoperative fluid balance and postoperative acute kidney injury (AKI) and other postoperative complications. Methods: We included consecutive adult liver transplant recipients who had their surgery between July 2008 and December 2017. Our exposure was intraoperative fluid balance, and our primary outcome was the grade of AKI at 48 hours after surgery. Our secondary outcomes were the grade of AKI at 7 days, the need for postoperative renal replacement therapy, postoperative red blood cell transfusions, time to first extubation, time to discharge from the intensive care unit (ICU), and 1-year survival. Every analysis was adjusted for potential confounders. Results: We included 532 transplantations in 492 patients. We observed no effect of fluid balance on either 48-hour AKI, 7-day AKI, or on the need for postoperative renal replacement therapy after adjustments for confounders. A higher fluid balance increased the time to ICU discharge, and increased the risk of dying (hazard ratio = 1.21 [1.04, 1.40]). Conclusions: We observed no association between intraoperative fluid balance and postoperative AKI. Fluid balance was associated with longer time to ICU discharge and lower survival. This study provides insight that might inform the design of a clinical trial on fluid management strategies in this population. Abstract : Supplemental Digital Content is available in the text.